PROSES PEMBENTUKAN SIKAP SECARA BERJENJANG: STUDI EMPIRIS DI BIDANG PERLUASAN MEREK - Haryanto, Budhi (Journal of Indonesian Economy and Business, 2008)
This study examines goodness-of-fit model to explain brand extensionphenomenon. Specifically, explaining the influence of brand similarity, belief toward core brand, and motivation to elaborate information on attitude toward brand extension.Laboratory experiment was used to ascertain controlled variables. Participants consist of 598 undergraduate students in business. Hierarchical regression analysis was used to elaborate the linkage among these observed variables. The study shows that complexityof brand extension was linearly influenced by brand similarity, belief toward core brand, and motivation to elaborate information. The finding confirms that the decision toward brand extension was significantly tested. Implications for further research are alsodiscussed.Kata kunci: perluasan merek, sikap, perilaku konsumen, kognitif.